2007
DOI: 10.1007/s00442-007-0744-9
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of dissolved oxygen isotopic ratios: a transient model to quantify primary production, community respiration, and air–water exchange in aquatic ecosystems

Abstract: Dissolved O(2) is an important aquatic ecosystem health indicator. Metabolic and gas exchange (G) rates, which control O(2) concentration, are affected by nutrient loading and other environmental factors. Traditionally, aquatic metabolism has been reported as primary production:community respiration (P:R) ratios using diel measurements and interpretations of dissolved O(2) and/or CO(2) concentrations, and recently using stable isotopes (delta(18)O, Delta(17)O) and steady state assumptions. Aquatic ecosystems, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 67 publications
3
80
0
Order By: Relevance
“…3 in Venkiteswaran et al (2007). For each day, NEP was calculated as the difference between temperature-corrected GPP and R. The autocorrelation (ACF) and partial autocorrelation (PACF) functions for all three metabolic rates for each year indicated significant autocorrelation, especially at the 1-3 day lag for all models.…”
Section: Inter-annual Trend Analysismentioning
confidence: 99%
“…3 in Venkiteswaran et al (2007). For each day, NEP was calculated as the difference between temperature-corrected GPP and R. The autocorrelation (ACF) and partial autocorrelation (PACF) functions for all three metabolic rates for each year indicated significant autocorrelation, especially at the 1-3 day lag for all models.…”
Section: Inter-annual Trend Analysismentioning
confidence: 99%
“…The P/R ratios should be viewed with caution, as physical processes and diel variations can make the steady state model unreliable (Venkitsewaran et al 2007;Wang et al 2008), but comparisons with the results of oxygen light and dark bottle experiments in this study area in 2004 (S. Bocaniov unpublished data) and in Hamilton Harbour (western Lake Ontario) in 2003 and 2004 (Bocaniov et al 2012) indicated a substantial agreement between methods. Rather than an overriding influence of allochthonous DOM, the P/R ratios indicated a dual influence of allochthonous DOM and inorganic nutrients.…”
Section: (B) (A)mentioning
confidence: 99%
“…Unfortunately, both methods relied on timeconsuming incubations that would prevent large-scale studies such as those conducted across the Louisiana continental shelf. Furthermore, in some instances, the study by Venkiteswaran et al (2007) had to use extremely low ɛ values (−2.0‰) to produce a good agreement between observed and modeled data.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, two alternative models have been developed that use oxygen concentrations and stable isotopes values to characterize productivity in aquatic systems (Tobias et al 2007;Venkiteswaran et al 2007). These models attempt to fit model parameters to measured diurnal oxygen patterns.…”
Section: Discussionmentioning
confidence: 99%